Nonverbal learning disabilities at home : a parent's guide - Tanguay, Pamela B., 1947- (Jessica Kingsley Pub., 2001)
This book explores the problems children with NLD may face, and provides strategies for parents to help them cope and grow, from preschool age through their challenging adolescent years. The author provides solutions to the everyday challenges of the disorder, from early warning signs and self-care issues to social skills and personal safety.